2017
DOI: 10.3389/fphys.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Icing on Inflammation, Angiogenesis, Revascularization, and Myofiber Regeneration in Skeletal Muscle Following Contusion Injury

Abstract: Contusion injuries in skeletal muscle commonly occur in contact sport and vehicular and industrial workplace accidents. Icing has traditionally been used to treat such injuries under the premise that it alleviates pain, reduces tissue metabolism, and modifies vascular responses to decrease swelling. Previous research has examined the effects of icing on inflammation and microcirculatory dynamics following muscle injury. However, whether icing influences angiogenesis, collateral vessel growth, or myofiber regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…It has already been shown that cryotherapy can weaken or delay the infiltration of inflammatory cells (8,33), which could be explained by vasoconstriction caused by exposure to the cold. This causes the reductionof cellular permeability, and lymphatic and capillary vessels, and consequently reduces fluid propagation into the interstitial space (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that cryotherapy can weaken or delay the infiltration of inflammatory cells (8,33), which could be explained by vasoconstriction caused by exposure to the cold. This causes the reductionof cellular permeability, and lymphatic and capillary vessels, and consequently reduces fluid propagation into the interstitial space (34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low tissue temperature is the most powerful intervention towards limiting ischemia reperfusion injury (IRI), which may subsequently prevent mitochondrial damage and, therefore, reduce the severity of IRI (9). Basic animal studies have proved the positive effect of icing treatment over contusion injury (10) and crush injury in rats (11) in the early stages of attenuated inflammation (during migration of inflammatory cells); however, these effects were not sufficient to prevent effective muscle regeneration at later stages. Furthermore, such studies did not investigate and clarify the efficacy of icing intervention in improving survival, electrolyte balance, vital signs, and inflammation at early stages within 24 h.…”
Section: Icing Treatment In Rats With Crush Syndrome Can Improve Survmentioning
confidence: 99%
“…For example, cryotherapy, one widely popular postexercise recovery modality, appears to delay rather than improve recovery after a bout of eccentric exercise of the elbow flexors (50) as well as arm cycling exercise (8). In animal models of muscle injury, topical icing has been shown to delay the infiltration of inflammatory cells into the damaged muscle (45,47) and attenuate the expression of proangiogenic factors (45).…”
Section: Introductionmentioning
confidence: 99%